Peningkatan Mutu Pendidikan Muhammadiyah melalui Implementasi Kurikulum ISMUBA dan Profesionalisme Guru - Yunita Firnanda; Nabila Dwi Aqmalia; Abdul Kholid Achmad (Journal Islamic Studies of Muhammadiyah, 2026)
This study aims to provide a comprehensive analysis of the dynamics, challenges, and strategic efforts to improve the quality of Muhammadiyah education in the current era of disruption. The analysis focuses on a critical review of the implementation of the Al-Islam, Kemuhammadiyahan, and Arabic Language Curriculum (ISMUBA) as well as the factors shaping teacher professionalism. Since its establishment in 1912, Muhammadiyah has served as both an Islamic movement and an educational institution committed to reforming Islamic education in Indonesia by integrating religious knowledge with modern scientific disciplines, thereby cultivating ulama-intellectuals and intellectual-ulama. The study employs a qualitative literature review design by analyzing 20 PDF documents, consisting of official Muhammadiyah publications and peerreviewed journal articles. The analysis is further reinforced through descriptive correlational techniques to examine teacher professionalism data and is synthesized using the Miles and Huberman interactive model. The findings indicate that teaching experience has a positive and statistically significant effect on teacher professionalism, whereas educational attainment and training programs have yet to demonstrate significant influence. Revitalization strategies identified in this study include strengthening institutional networks, advancing global expansion, developing technology-driven educational programs (such as Muhammadiyah Online University), and revitalizing ISMUBA/AIK as a foundation for ideological strengthening and cadre development. In conclusion, the study argues that Muhammadiyah education possesses substantial potential to excel in the disruptive era, provided that the organization’s reformist spirit (tajdid) is holistically integrated into curriculum development, learning methodologies, and teacher professionalism enhancement efforts.   ABSTRAK. Penelitian ini bertujuan menganalisis secara komprehensif dinamika, tantangan, dan strategi peningkatan mutu pendidikan Muhammadiyah, terutama di era disrupsi, melalui telaah kritis terhadap implementasi Kurikulum Al-Islam, Kemuhammadiyahan, dan Bahasa Arab (ISMUBA) serta faktor profesionalisme guru. Muhammadiyah, sebagai gerakan Islam dan pendidikan sejak 1912, secara historis hadir sebagai upaya pembaharuan pendidikan Islam di Indonesia, mengintegrasikan ilmu agama dan ilmu umum untuk mencetak ulama-intelektual atau intelektual-ulama. Kajian ini menerapkan metode studi pustaka kualitatif dengan menganalisis 20 dokumen PDF, meliputi dokumen resmi Muhammadiyah dan jurnal ilmiah. Analisis diperkuat dengan teknik deskriptif korelasional untuk menguji data profesionalisme guru, dan disintesis menggunakan model Miles dan Huberman. Temuan menunjukkan bahwa pengalaman mengajar memiliki pengaruh positif dan signifikan terhadap profesionalisme guru, sementara jenjang pendidikan dan pelatihan belum menunjukkan pengaruh signifikan. Strategi revitalisasi mencakup penguatan jaringan, ekspansi global, pengembangan program berbasis teknologi (seperti Muhammadiyah Online University), dan revitalisasi ISMUBA/AIK untuk menguatkan ideologi dan kaderisasi. Kesimpulannya, pendidikan Muhammadiyah berpotensi unggul di era disrupsi jika komitmen terhadap pembaharuan (tajdid) diterapkan secara holistik pada kurikulum, metode pembelajaran, dan profesionalisme guru.